In vitro investigations of propulsion during laser lithotripsy using video tracking. Issue 4 (20th December 2017) - Eisel, Maximilian; Ströbl, Stephan; Pongratz, Thomas; Strittmatter, Frank; Sroka, Ronald
Abstract : Objectives: Ureteroscopic laser lithotripsy is an important and widely used method for destroying ureter stones. It represents an alternative to ultrasonic and pneumatic lithotripsy techniques. Although these techniques have been thoroughly investigated, the influence of some physical parameters that may be relevant to further improve the treatment results is not fully understood. One crucial topic is the propulsive stone movement induced by the applied laser pulses. To simplify and speed up the optimization of laser parameters in this regard, a video tracking method was developed in connection with a vertical column setup that allows recording and subsequently analyzing the propulsive stone movement in dependence of different laser parameters in a particularly convenient and fast manner. Materials and Methods: Pulsed laser light was applied from below to a cubic BegoStone phantom loosely guided within a vertical column setup. The video tracking method uses an algorithm to determine the vertical stone position in each frame of the recorded scene. The time‐dependence of the vertical stone position is characterized by an irregular series of peaks. By analyzing the slopes of the peaks in this signal it was possible to determine the mean upward stone velocity for a whole pulse train and to compare it for different laser settings. For a proof of principle of the video tracking method, a specific pulse energy setting (1 J/pulse) was used in combination with three different pulse durations: short pulse (0.3 ms), medium pulse (0.6 ms), and long pulse (1.0 ms). The three pulse durations were compared in terms of their influence on the propulsive stone movement in terms of upward velocity. Furthermore, the propulsions induced by two different pulse energy settings (0.8 J/pulse and 1.2 J/pulse) for a fixed pulse duration (0.3 ms) were compared. A pulse repetition rate of 10 Hz was chosen for all experiments, and for each laser setting, the experiment was repeated on 15 different freshly prepared stones. The latter set of experiments was compared with the results of previous propulsion measurements performed with a pendulum setup. Results: For a fixed pulse energy (1 J/pulse), the mean upward propulsion velocity increased (from 120.0 to 154.9 mm · s −1 ) with decreasing pulse duration. For fixed pulse duration (0.3 ms), the mean upward propulsion velocity increased (from 91.9 to 123.3 mm · s −1 ) with increasing pulse energy (0.8 J/pulse and 1.2 J/pulse). The latter result corresponds roughly to the one obtained with the pendulum setup (increase from 61 to 105 mm · s −1 ). While the mean propulsion velocities for the two different pulse energies were found to differ significantly ( P < 0.001) for the two experimental and analysis methods, the standard deviations of the measured mean propulsion velocities were considerably smaller in case of the vertical column method with video tracking (12% and 15% for n = 15 freshly prepared stones) than in case of the pendulum method (26% and 41% for n = 50 freshly prepared stones), in spite of the considerably smaller number of experiment repetitions ("sample size") in the first case. Conclusion: The proposed vertical column method with video tracking appears advantageous compared to the pendulum method in terms of the statistical significance of the obtained results. This may partly be understood by the fact that the entire motion of the stones contributes to the data analysis, rather than just their maximum distance from the initial position. The key difference is, however, that the pendulum method involves only one single laser pulse in each experiment run, which renders this method rather tedious to perform. Furthermore, the video tracking method appears much better suited to model a clinical lithotripsy intervention that utilizes longer series of laser pulses at higher repetition rates. The proposed video tracking method can conveniently and quickly deliver results for a large number of laser pulses that can easily be averaged. An optimization of laser settings to achieve minimal propulsive stone movement should thus be more easily feasible with the video tracking method in connection with the vertical column setup. Lasers Surg. Med. 50:333–339, 2018. © 2017 Wiley Periodicals, Inc.